Convergence Behavior for Newton-Steffensen’s Method under -Condition of Second Derivative - Yonghui Ling; Xiubin Xu; Shaohua Yu (Abstract and Applied Analysis)
The present paper is concerned with the semilocal as well as the local convergence problems of Newton-Steffensen’s method to solve nonlinear operator equations in Banach spaces. Under the assumption that the second derivative of the operator satisfies -condition, the convergence criterion and convergence ball for Newton-Steffensen’s method are established.